Access and control of biodiversity in the context of biopiracy: the case of pelargonium sidoides in the Raymond Mhlaba Local Municipality - Doyle, Anastasia Roxane (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
The purpose of this research is to explore access and control of biodiversity in the context of biopiracy with specific reference to the case of pelargonium sidoides in the Raymond Mhlaba Local Municipality. The research is informed by the increased appropriation of local biodiversity and indigenous knowledge by industry as well as global debates on promoting sustainable resource utilisation and sustainable rural livelihoods. This study adopts a two-pronged conceptual approach mainly, Marx's Ecology and the Sustainable Rural Livelihoods Framework (SRLF). The former provides useful insights into the processes and dynamics of power asymmetries between developed and developing countries, capital accumulation, inherent displacement and the predatory nature of capitalism. Whilst the latter addresses how livelihoods are fashioned in a holistic way. As a significant starting point the South African political economy is examined through the lens of the two economies debate. This research is primarily qualitative using in-depth interviews, observations and archival research as the primary data collection techniques. Preliminary site visits were conducted to negotiate access. Key informants of the study were representatives of the core groups (interested and affected stakeholders) involved in the case of pelargonium sidoides. Specifically, participants included representatives from the Imingcangathelo Community Development Trust and the Masakhane Community Property Association, local harvesters, local community members, monitoring and enforcement environmental officers, plant breeders (cultivators), scientists, local businessmen involved in natural resource trade, academics, legal representatives and non-governmental organisations. The Rhodes University research ethical guidelines were followed accordingly. The findings of the study suggest that trade in pelargonium sidoides is influenced by a complex and dynamic interplay between the state-industry-rural elite coalitions. Moreover, that this activity is largely centralised and exclusionary. This process is depicted in the unsustainable utilisation of pelargonium sidoides and other natural resources, the dismantling of local livelihoods, exploitation of harvesters and an incoherent environmental governance structure. At the core of this unequal system of exchange is industry, which effectively functions to generate profits whilst dispossessing peripheral communities such as the Masakhane community. The study therefore, argues that in order for local communities to access the trade there needs to be a shift in this system of unequal exchange. Not only regarding beneficiation, but in building community capacity and becoming involved as critical stakeholders in the governance of resources in the study area. The study found that there are competing narratives that inform the status and sustainability of pelargonium sidoides. Furthermore, given the current trajectory of the Masakhane community's struggle for land, access to natural resources and exclusion from decision-making regarding pelargonium sidoides, the area will continue to be underdeveloped with concomitant poverty, inequality and comprised rural livelihoods.
Keywords: Biopiracy -- South Africa; Traditional ecological knowledge -- South Africa; Plants, Cultivated -- Patents; Biodiversity -- Conservation -- South Africa; Pelargoniums -- Harvesting -- South Africa; Pelargonium sidoides -- Harvesting -- South Africa